Konsep Pendampingan dalam Struktur Pemerintahan Indonesia: Mengapa Pendamping Lokal Desa Harus Ada? - Rambe, Jenny Yelina; Badaruddin, Badaruddin; Kadir, Abdul (Universitas Medan Area, 2020)
Rural development is a priority of national development program in Indonesia. A number of measures have been taken such as decentralization of authority, capacity building, and budget approach. The most recently used action to accelerate rural development is through the village assistance program. Each village has a local village assistant to optimize the village administration performance and build the village community capacity in the rural development process. This research aims to explore the concept of village assistance program and the role of local village assistants in Batu Layan Village, Padangsidempuan City, North Sumatra Province. This research used qualitative research. The data were obtained through in-depth interviews, library research, and documentation studies. The research results indicated that the concept of village assistance was applied in stages following the governance structure in Indonesia to encourage the realization of the functions and authorities of each government structure in achieving development targets. Village local assistants in this research were able to perform their functions skillfully through a persuasive communication approach based on local values in the local area.